12th INTERNATIONAL CERAMICS CONGRESS PART D 2010
DOI: 10.4028/www.scientific.net/ast.65.263
|View full text |Cite
|
Sign up to set email alerts
|

Constrained and Non-Constrained Sintering of Plasma-Sprayed Zirconia Based Electrolytes for SOFCs

Abstract: Electrolyte layers for solid oxide fuel cells (SOFCs) consisting typically of yttria-stabilized zirconia were prepared using atmospheric plasma spraying in a first step and sintered in a second one. The influence of particle size on sintering kinetics and microstructure development was analyzed by comparison of nanostructured and conventional YSZ layers. Sintering of free-standing coatings differ significantly from that of coatings on substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…There are various other studies which have shown the effect of sintering on reduction in porosity content and volume shrinkage. [30][31][32][33][34] Ilavsky's small angle scattering study suggests that certain types of pores and interfaces can undergo localized sintering even at 800°C to 900°C consistent with the knowledge of diffusion kinetics in YSZ. However, the implications of these low-temperature (<1000°C) microstructure changes on the elastic properties have not be studied, especially given that the coating has 8-9 times lower bending modulus than their completely dense counterparts largely due to the high porosity content and imperfect bonding between splats.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…There are various other studies which have shown the effect of sintering on reduction in porosity content and volume shrinkage. [30][31][32][33][34] Ilavsky's small angle scattering study suggests that certain types of pores and interfaces can undergo localized sintering even at 800°C to 900°C consistent with the knowledge of diffusion kinetics in YSZ. However, the implications of these low-temperature (<1000°C) microstructure changes on the elastic properties have not be studied, especially given that the coating has 8-9 times lower bending modulus than their completely dense counterparts largely due to the high porosity content and imperfect bonding between splats.…”
Section: Introductionsupporting
confidence: 66%
“…They found the surface area of cracks and voids kept decreasing beyond 600°C and almost 33% of surface area of voids and microcracks have been lost from as sprayed coating to 1000°C heat‐treated coating. There are various other studies which have shown the effect of sintering on reduction in porosity content and volume shrinkage …”
Section: Introductionmentioning
confidence: 99%
“…The thermal expansion of the crystal lattice is the result of the increased vibration amplitude of the ions in the lattice nodes, caused by the temperature increase [3].…”
Section: The Dilatometry Analysis Results For the Obtained Coatingsmentioning
confidence: 99%